Evaluation of Shallow Groundwater Resources between Alross and Alsharasheer rivers - اسماعيل أمل; علي الأسعد (Latakia University Journal -Engineering Sciences Series, 2023)
The Jableh Plain faces an important economic activity, which lead to growing water demands. The studied area constitutes part of it. The study area is about 12 km2. The research aims to evaluate the groundwater resources, and calculating the water budget. The study depends on monthly field observation of water table depths in the wells of the monitoring network, which consists of 36 wells . Based on the analysis of changes in groundwater levels. It was observed that the rise of levels corresponds to changes in precipitation, due to the good permeability of the layer, This indicates that the recharge water plays an important role in the transfer of pollutants to the groundwater, The results of water balance shows that more than 40,000 m3 of water drain into rivers and sea, which can be used without harming the environment. Therefore, it is necessary to develop optimal plans for its investment.